Development of SDG-Oriented Natural and Social Sciences Teaching Materials Using Mind Mapping for Grade IV Elementary School Students - Idrus Salam; Ramalis Hakim; Darmansyah; Zelhendri Zen (Postgraduate, University of Mataram, 2026)
This research aims to develop valid, effective, and practical teaching materials based on mind mapping for Natural and Social Sciences (IPAS) subjects for fourth grade elementary school students, which is motivated by low learning outcomes and student motivation due to the use of less interesting conventional materials. The method used is development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), with data collected through class observation, interviews, expert validation, questionnaires, as well as pre-tests and post-tests. The results of validation by material, media, and language experts show that the teaching material is very valid with Aiken's V scores of 0.97, 0.89, and 0.97, respectively. An effectiveness test with an N-Gain score showed a significant improvement in learning outcomes, with scores of 0.7765 (small group) and 0.7971 (large group), both in the high category. The paired sample t-test showed a significance value of p = 0.000 (< 0.05), indicating a significant difference between the pre-test and the post-test. In terms of practicality, the teaching materials received a very positive response from teachers (96.36%) and students (93.25%), which showed that the materials were easy to use, interesting, and helped the understanding of IPAS concepts. Thus, the mind mapping-based teaching materials developed in this study have proven to be feasible to improve the quality of science learning in fourth grade basic education.